Analisis Viktimologi terhadap Anak Korban Pemerkosaan yang dilakukan Seorang Kakek : Studi Kasus di Kota Atambua, Belu Nusa Tenggara Timur - Adriana Febiola Letto; Jimmy Pello; Thelma S. M. Kadja (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This study aims to find out and analyze the victimology of child rape victims in the city of Atambua. The research method used in this writing is empirical legal research obtained through interviews and document studies. The results of the study showed: (1) The form of protection of rights for child victims of rape which includes: the form of protection of victims' rights, law enforcement and response of the Women's Empowerment and Rights Protection Office of Belu Regency regarding rape cases in Tulamalae, Atambua, Belu. (2) Efforts Made in Overcoming Child Rape Cases in Atambua City which include: Efforts and Assistance Provided by Safe Homes and Responses and Actions of the Belu Regency Women's Empowerment and Rights Protection Office Outside the Protection House/Safe House. Women's Empowerment and Rights Protection Office Outside the Protection House/Safe House.